Determinan Kejadian Kelelahan Kerja Kronis (burnout) pada Pekerja BPJS Kesehatan Cabang Batam - Miranda Ramadhanty Fakhri; Novikasari Novikasari; Rico Januar Sitorus (LPPM Institut Pendidikan Nusantara Global, 2025)
Chronic work fatigue (burnout) is a condition of physical, emotional, and mental exhaustion resulting from prolonged work demands, particularly in the public service sector. Employees of BPJS Kesehatan are at risk of experiencing burnout due to the intensity of interactions with participants, administrative pressures, and service performance demands. This study aimed to analyze the relationship between individual characteristics, emotional intelligence, physical activity, workload, dietary patterns, and nutritional status with the occurrence of chronic work fatigue (burnout) among employees of BPJS Kesehatan Batam Branch. This study used a cross-sectional design with a total of 100 respondents. Data analysis was conducted using univariate, bivariate, and multivariate analyses with multinomial logistic regression. The results showed that the majority of respondents experienced chronic work fatigue (burnout) at a moderate level, followed by a high level, while only a small proportion experienced a low level. Bivariate analysis showed significant relationships between age, marital status, educational level, length of employment, and workload with burnout (p < 0.05). Meanwhile, emotional intelligence, physical activity, dietary patterns, meal frequency, nutritional status, work unit, and job position did not show statistically significant relationships. In multivariate analysis, only gender was proven to be significantly associated with high-level burnout compared to low-level burnout after controlling for other variables (p < 0.05). This study concludes that chronic work fatigue among employees of BPJS Kesehatan Batam Branch is influenced by certain factors, with gender as the dominant factor. It is recommended that BPJS Kesehatan strengthen burnout prevention strategies through workload management, organizational support, and sustainable workplace health promotion programs.